Ecological Factors Determining Barking Deer Distribution and Habitat Use in the Mid-Hills of Nepal - Neupane, Bijaya; Dhami, Bijaya; Bista, Shreyashi; Sadadev, Bipana Maiya; Regmi, Siddhartha; Shrestha, Sami; Shrestha, Bikram; Traxmandlová, Iva; Varachova, Sona; Kindlmann, Pavel (Frontiers in Ecology and Evolution, 2022)
Barking deer is found in dense tropical and subtropical forests of Asia. It is listed as “least concerned” by the IUCN and as “vulnerable” in Nepal, where it is also protected. Due to the habitat loss and fragmentation by human activities, barking deer abundance is decreasing, which may even ultimately lead to its extinction. This in turn might negatively affect local ecosystem such as the abundance of the endangered common leopard, for which barking deer is the main prey species in the mid-hills of Nepal. We therefore need to know factors affecting barking deer abundance and its habitat preferences. To determine these factors, we used transect surveys and measured main four ecological drivers such as forest management regime, microclimate, disturbance and food resources, which include 11 habitat characteristics in spots where barking deer was present, and in randomly selected spots. We found that elevation, slope, distance to settlement, presence of tree species, depth of leaf litter and percentage cover of leaf litter were most significantly affecting its presence. These results can serve as guidelines for local authorities to prevent decline in abundance of barking deer.